Penerapan Realistic Mathematics Education untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika di Sekolah Dasar - Alivi Lutfil Karimah; Sudarmiatin Sudarmiatin; Edy Bambang Irawan (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: This research was aimed to improve the problem-solving ability of mathematics in elementary school by applying Realistic Mathematics Education. This reserach uses action research design Geofrey E. Mills model  through identify an area focus, collect data, analyse and interprete data, develope an action plan. the research was held on grade IV SDN Blimbing 1 with 39 student. The reserach instrumen was used obsevation sheet of teacher activity and student activity, observation sheet of problem-solving abilities, problem-solving abilities test, interview sheets, and field notes. The research findings show that there is an increase of problem solving ability of 88% due to the addition of treatment as a result of reflection in cycle I. Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan pemecahan masalah matematika di Sekolah Dasar dengan menerapkan Realistic Mathematics Education. Penelitian ini menggunakan desain penelitian tindakan kelas model Geofrey E. Mills melalui identify an area focus, collect data, analyse and interprete data, develope an action plan. Subjek penelitian adalah siswa kelas IV SDN Blimbing 1 yang berjumlah 39 siswa. Instrumen penelitian yang digunakan adalah lembar observasi kegiatan guru dan siswa, lembar observasi kemampuan pemecahan masalah, soal tes kemampuan pemecahan masalah, lembar wawancara, dan catatan lapangan. Temuan penelitian menunjukkan bahwa terdapat peningkatan kemampuan pemecahan masalah sebesar 88% karena penambahan treatment sebagai hasil refleksi pada siklus I.